The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.7554/elife.49972
|View full text |Cite
|
Sign up to set email alerts
|

Giant extinct caiman breaks constraint on the axial skeleton of extant crocodylians

Abstract: The number of precaudal vertebrae in all extant crocodylians is remarkably conservative, with nine cervicals, 15 dorsals and two sacrals, a pattern present also in their closest extinct relatives. The consistent vertebral count indicates a tight control of axial patterning by Hox genes during development. Here we report on a deviation from this pattern based on an associated skeleton of the giant caimanine Purussaurus, a member of crown Crocodylia, and several other specimens from the Neogene of the northern n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Likewise, according to nearly all recent phylogenetic analyses (Scheyer et al . 2019; Cidade et al . 2020a), the known representatives of the earliest divergent caimanine lineages (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, according to nearly all recent phylogenetic analyses (Scheyer et al . 2019; Cidade et al . 2020a), the known representatives of the earliest divergent caimanine lineages (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Crown-group crocodylians share the same number of precaudal vertebrae (9 cervical, 15 dorsal, and 2 sacral vertebrae: Reese 1915 ; Mook 1921b ; Hoffstetter and Gasc 1969 ; Iijima and Kubo 2019 ), allowing the body size estimation based on incompletely preserved precaudal vertebrae. Recently, sacralization of the last dorsal vertebra was reported in a Miocene caimanine Purussaurus mirandai ( Scheyer et al. 2019 ), although it would not change the total number of precaudal vertebrae.…”
Section: Introductionmentioning
confidence: 99%
“…Hutchinson et al (2019) observed that crocodylian species reduce speed and eventually lose any asymmetrical gait capacity at only moderate sizes (and probably during ontogeny). Giant (1000-3000+ kg; Table S1) extant and extinct Crocodylia can still walk terrestrially and there has been little study of how they maintain this modest capacity (but see Scheyer et al, 2019). Giant rodents are another captivating case study.…”
Section: Water-land Transitions Gravity and Giantsmentioning
confidence: 99%